A review of the genus Aalatettix with the description of a new species from China (Orthoptera: Tetrigidae) - Zheng, Zhemin; Lin, Liliang (Zootaxa, 2015)
A new species, i.e., Aalatettix nyalamensis sp. nov. is described from the Xizang Autonomous Region of China. All seven known species of genus, including A. nyalamensis sp. nov., were reviewed and a key to species of the genus Aalatettix is given. Type specimens are deposited in the Institute of Zoology, Shaanxi Normal University.